The Mechanism of Interaction of the Judicial Authority of Ukraine with the Public - Krutii, Olena; Klimova, Svitlana (Theory and Practice of Public Administration, 2023)
The current state of society is characterized by the expansion of the conflict space, the increase in tension in social relations between the judicial authorities and the public. It is precisely because of this that issues of improving the mechanism of interaction between judicial institutions and public associations and active citizens are being brought into focus. The purpose of this research is to substantiate theoretical and methodological principles and develop a mechanism of interaction between the judiciary of Ukraine and the public as a basis for making rational administrative decisions. The subject of the study is the relationship between judicial authorities and public associations and citizens regarding management decision-making. The object of the research is normative documents, recommendations and strategic documents regulating the issue of administrative decision-making in the judicial institutions of Ukraine, as well as academic publications and analytical reports on the issues, which are under consideration in this article. The research methodology combines a complex of modern philosophical, general scientific, special scientific methods of cognition, including dialectical, systemic, structural-functional, classification, etc. While processing the scientific sources and legislation in order to thoroughly study the subject of research, highlight its properties, the method of analysis was used. The article examines the mechanism of interaction between the judiciary and the public and establishes the elements of such a mechanism. Based on the analysis of normative-and-legal acts and the effectiveness of the activities of judicial authorities, strategies for the development of the judicial branch of government in Ukraine, the directions to improve the mechanism of interaction of citizens with the independent branch of government - the judiciary, with the aim of exerting their influence on the process of making administrative decisions - have been determined. The interaction of judicial authorities with the public is becoming more and more important every year, the influence of public opinion on administrative decisions is increasing, and because of this, the mechanism of such interaction is being improved and the state’s relations with the public are being reformatted, the gradual introduction of international standards and best practices of the Council of Europe and the European Union in system of justice and public administration of Ukraine. Mandatory elements of the mechanism of interaction of the judiciary with the public are not only the subject-object composition, but also the goals, principles, functions, forms of interaction, information and methods of its presentation, technologies and technical means. The task of the operation of such a mechanism is defined as ensuring the adoption of rational administrative decisions by the Higher Qualification Commission of Judges of Ukraine, the State Judicial Administration of Ukraine, court apparatuses and other institutions of the judicial branch of government in cooperation with the public. Taking into account the wide differentiation of interaction between various subjects of management in the sphere of justice, we consider it necessary to further define the types and forms of such interaction, which has not only methodological, but also practical significance, as it contributes to its normalization according to certain signs or criteria, which allows to effectively determine methods of its practical implementation. The improvement of the mechanism of interaction between the judiciary and the public is in: 1) reducing the number of conflicts and transferring interaction to the level of real and effective cooperation; 2) increasing the openness of the State Judicial Administration of Ukraine and court apparatuses, their readiness for dialogue with the public; 3) granting the Public Integrity Council more powers to influence the career of judges.